Les disparités économiques au sein du Tiers-Monde : quelques constats à propos du Maghreb et des pays de l’Asie du Sud-Est - Ibtissem Omri (L’Année du Maghreb)
The purpose of our research is to highlight the sharp economic disparities observed both between major international countries and between developing countries, and thus challenge the neoclassical conclusions about the convergence of nations. We focused our study primarily on third-world disparity and tried to classify developing countries into three mixed groups, with South-East Asia as the fastest economically growing group. A brief comparative study between North Africa (Tunisia and Morocco) and South-East Asia (South Korea and Malaysia) clearly shows that the differences between these two groups tend to increase over time.